Stabilitas Produksi Sepuluh Genotip Padi Sawah di Lahan Salin - , Intan; Agus Riyanto; Noor Farid; , Suprayogi; Totok Agung D. H. (Zuriat, 2012)
Diversity of the physical environment which is followed by the diversity of genetic resources in agriculture in Indonesia is very wide. The potential of specific environments can be used by breeders in determining the applicability distribution of a superior new cultivars, such as releasing the rice cultivars tolerant salinity with high yield potential for a wide range of spatial and specific. We growed 10 genotypes of rice and Siak Raya as check in three locations with low to moderate levels of salinity, Kebumen (140 µc/cm-350 µc/cm), Batang (861 µc/cm-5783 µc/cm), dan Pekalongan (670 µc/cm-1416 µc/cm). Genotypes showed difference performance, which indicated diversity of agronomic characters at three location. Genotypes stability were tested refer to Eberhart and Russell (1963), UNSOED 8 is a stable genotype with higher gran yield than the total average of genotypes.